A new species of Thalictrum (Ranunculaceae) from southern Tibet (Xizang), China - Li, Jin-Yu; Xie, Lei; Li, Liang-Qian (Phytotaxa, 2015)
The new species Thalictrum austrotibeticum (Ranunculaceae) from southern Tibet (Xizang), China, is here described and illustrated. It occurs in forest margin and grassy slopes of several valleys of southern Xizang along the central Himalayas. This species is morphologically well differentiated from other Thalictrum species from south-west China, Bhutan, Nepal, and Northern India. From its floral characters, this species shows some relationship with Th. finetii. A key of Thalictrum species distributed in southern Xizang and adjacent areas of Bhutan, Nepal, and India is also provided.